Enriching Women's Poor Political Education - Matroni; Moh. Toyu (CV. Intake Pustaka, 2025)
This research focuses on the study of Islam from a philosophical perspective using a theoretical framework. Education and the modern Islamic historical approach of Ibrahim Abu Rabi', with the aim of enriching the philosophical horizon related to contemporary problems, namely women's education, while the methodology in this study uses qualitative methods, with the conclusion that to read the problems of Islamic education today, we must open the tap of modern Islamic history as the forerunner to the development of Islamic education today which continues to experience change and development